Local Antigen Encounter Is Essential for Establishing Persistent CD8+ T-Cell Memory in the CNS - Schøller, Amalie S.; Fonnes, Masja; Nazerai, Loulieta; Christensen, Jan P.; Thomsen, Allan R. (Frontiers in Immunology, 2019)
While the brain is considered an immune-privileged site, the CNS may nevertheless be the focus of immune mediated inflammation in the case of infection and certain autoimmune diseases, e.g., multiple sclerosis. As in other tissues, it has been found that acute T-cell infiltration may be followed by establishment of persistent local T-cell memory. To improve our understanding regarding the regulation of putative tissue resident memory T (Trm) cells in CNS, we devised a new model system for studying the generation of Trm cells in this site. To this purpose, we exploited the fact that the CNS may be a sanctuary for adenoviral infection, and to minimize virus-induced disease, we chose replication-deficient adenoviruses for infection of the CNS. Non-replicating adenoviruses are known to be highly immunogenic, and our studies demonstrate that intracerebral inoculation causes marked local T-cell recruitment, which is followed by persistent infiltration of the CNS parenchyma by antigen specific CD8+ T cells. Phenotypical analysis of CNS infiltrating antigen specific CD8+ T cells was consistent with these cells being Trms. Regarding the long-term stability of the infiltrate, resident CD8+ T cells expressed high levels of the anti-apoptotic molecule Bcl-2 as well as the proliferation marker Ki-67 suggesting that the population is maintained through steady homeostatic proliferation. Functionally, memory CD8+ T cells from CNS matched peripheral memory cells with regard to capacity for ex vivo cytotoxicity and cytokine production. Most importantly, our experiments revealed a key role for local antigen encounter in the establishment of sustained CD8+ T-cell memory in the brain. Inflammation in the absence of cognate antigen only led to limited and transient infiltration by antigen specific CD8+ T cells. Together these results indicate that memory CD8+ T cells residing in the CNS predominantly mirror previous local infections and immune responses to local autoantigens.